Comparison of Motor Skills of Children with Down Syndrome, Intellectual Disability, and Autism Spectrum Disorder - Fahimeh Adibsaber; Soleyman Ansari Kolachahi; Akbar Allahyari Karnagh; Rajab Ali Ahmadi; Babak Barkadehi (University of Tehran, 2023)
.Introduction: This study aimed to compare motor skills in four groups of intellectual disability, Down syndrome, autism spectrum, and normal children.Methods: The research method was descriptive and causal-comparative. The statistical population of this study included children aged 7 to 12 from centers for special needs in Rasht City in 2022. One hundred people (25 participants for each group) were considered as statistical samples. Eight sub-tests of the shortened form of Bruininks-Oseretsky Test of Motor Proficiency - Second Edition (BOT-2) were used to collect data. Analysis of variance test was used to analyze the research data at the significance level of 0.05.Results: The results showed that in the sub-tests of movement speed and agility, balance, strength, reaction time, upper limb dexterity, and the total score of motor proficiency, the performance of children with autism spectrum and Down syndrome was weaker than the other two groups (P=0.001). There was no significant difference between the two groups of normal and intellectually disabled children in the balance and strength subtests (P>0.05). Also, in bilateral coordination and visual-motor control subtests, children with autism had a weaker performance than the other three groups (P=0.001), and no significant difference was observed between the other three groups (P>0.05).Conclusion: Considering the poor motor skills of children with autism spectrum and Down syndrome, and the effect of motor skills on social, academic, and learning skills, it seems necessary to include motor skills training and exercises for children with special needs at younger ages in educational programs of special schools and occupational therapy centers.